Microbiological profile and antibiotic susceptibility pattern in Blood stream infections in patients with Acute Cholangitis: A prospective observational study - Saqeb, Khan Md Nazmus (Bangladesh Critical Care Journal, 2020)
Background: I analyzed the organisms isolated from the blood of patients with acute cholangitis and determined their antibiotic resistance characteristics. In addition, I evaluated risk factors associated with antibiotic-resistant bacteria and their impact on clinical outcomes. Methods: 113 consecutive cases of acute cholangitis who met the diagnostic criteria were included in the study. Acute cholangitis was defined by TG18 criteria. Blood culture was obtained from every patient. The microbiological results of blood cultures & the antibiotic susceptibility pattern of the organisms were analyzed by SPSSv22.0. Multivariate analysis was performed to identify risk factors associated with antibiotic resistance & mortality. Result: Among 113 patients, 71(62.8%) were male & the median age was 51 years. Choledocholithiasis was the most common underlying biliary disease followed by malignant and benign strictures. Severe cholangitis occurred in 17(15%) cases. 32(28.3%) cases had nosocomial infection. Causative organisms were isolated from 55(48.7%) of 113 blood cultures. Escherichia coli was the most common bacterium isolated (36.36%) from blood, followed by Klebsiella pneumoniae (23.64%), Pseudomonas aeruginosa (7.27%) & Enterococcus (7.27%). Anaerobic bacteria were isolated from 5(9.09%) specimens. Multiple organisms were isolated in 6(10.91%) specimens. Most organisms were susceptible to meropenem (86.7%), imipenem (83.1%), colistin (89.1%), amikacin (76.1%), piperacillin-tazobactam (79.6%) & polymyxin-B (83.3%). Multidrug resistant bacteria comprised 30.91% of blood isolates. Risk factors associated with antibiotic resistance were presence of an indwelling biliary device (OR:7.7), prior biliary intervention (OR:6.167) and a nosocomial source of infection (OR:9.09). Thirteen (11.5%) patients died from acute cholangitis. Risk factors associated with mortality were severe cholangitis (OR:6.9), malignant biliary obstruction (OR:8.4), nosocomial infection (OR:7.5) and isolation of multidrug resistant organisms in blood (OR:6.9). Conclusion: E. coli was the most common organism isolated, followed by Klebsiella, Pseudomonas & Enterococcus. Colistin, meropenem, polymyxin-B, imipenem, amikacin & piperacillin-tazobactam were the most effective of all antibiotics. Risk factors associated with isolation of multidrug resistant bacteria from blood were presence of an indwelling biliary device, prior biliary intervention and a nosocomial source of infection. Risk factors associated with mortality were severe cholangitis, malignant biliary obstruction, nosocomial infection and isolation of multidrug resistant organisms in blood. Bangladesh Crit Care J September 2020; 8(2): 68-75